Prokaryotic soluble expression and purification of bioactive human fibroblast growth factor 21 using maltose-binding protein. Issue 1 (December 2017) - Nguyen, Anh; Song, Jung-A; Nguyen, Minh; Do, Bich; Kwon, Grace; Park, Sang; Yoo, Jiwon; Jang, Jaepyeong; Jin, Jonghwa; Osborn, Mark; Jang, Yeon; Vu, Thu; et al.
Abstract Human fibroblast growth factor 21 (hFGF21) has been characterized as an important regulator of glucose and lipid metabolism homeostasis. Here, to produce hFGF21 efficiently inEscherichia coli, the expression and solubility of hFGF21 were tested and optimised by fusing the protein with one of eight tags: hexahistidine (His6), thioredoxin (Trx), small ubiquitin-related modifier (Sumo), glutathione S-transferase (GST), maltose-binding protein (MBP), N-utilisation substance protein A (NusA), human protein disulphide isomerase (PDI), and the b′a′ domain of PDI (PDIb′a′). Each tag increased solubility of the protein when the expression temperature was 18°C. Unlike many other tags that were tested, MBP significantly enhanced the solubility of the protein also in the culture condition at 37°C. Thus, the MBP-hFGF21 construct was further pursued for optimisation of affinity chromatography purification. After tag removal, 8.1 mg of pure hFGF21 was obtained as a final product from 500 mL of starting culture. The protein was then characterised by mass spectroscopy and anin vitro functional assay using NIH-3T3 cells transfected with a β-klotho reporter gene. These characteristics are similar to those of commercial hFGF21. Thus, the MBP tag is useful for efficient prokaryotic production and purification of bioactive hFGF21.